ANALISIS HASIL BELAJAR BERDASARKAN KOMPONEN PROSES LITERASI MATEMATIKA - Rusmining Rusmining (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
This research is a descriptive qualitative research, with aims to describe the learning outcomes of mathematics based on the process components of the mathematical literacy. Process components are one of three components of assessment according to the International Student Assessment Program (PISA). The process components tested in this study include (1) ability to formulate problems, (2) ability to use concepts, facts, procedures and reasoning, and (3) ability to interpret results. The method used includes of documentation, observation, and interviews, with  triangulation techniques used as validity data. The results of this descriptive qualitative study are: (1) literacy ability in process of formulating problem obtains with average score of 23,33 from 25 maximum score. Its means the students are good at formulating the problems presented in the question. (2) Literacy ability of using concepts, facts, procedures and reasoning gets 30,63 average score from 50 maximum score . Its means students are not fully able to use conceptual skills, procedures properly. (3) Literacy ability in interpreting the results gets 15,73 average score from 25 maximum score. Its means the students are not fully able to interpret and evaluate the results of their work correctly. Among of the three process components, the conclution is the ability to formulate problems is most prominent compared to other process capabilities.